Talak Tiga Sekali Ucap: Kajian Gerakan Ganda Fazlur Rahman terhadap Hadis Hukum - Dini Tri Hidayatus Sya’dyya; Idri Idri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The hadith concerning triple divorce in a single pronouncement is one of the legal hadiths that has generated differing views among Islamic scholars. During the time of Prophet Muhammad (PBUH), Abu Bakr, and the early caliphate of ʿUmar ibn al-Khaṭṭāb, such a pronouncement was considered as a single divorce. However, ʿUmar later ruled that it should be counted as three, as a form of contextual ijtihād. This study aims to examine the hadith using Fazlur Rahman’s “double movement” approach, which emphasizes the importance of understanding the historical context of the text while applying the universal ethical values of Islam to contemporary situations. Through this approach, it is found that Islamic law is not static, but open to reform as long as it aligns with the fundamental moral principles of Islam. Fazlur Rahman views this hadith as evidence of the flexibility of Islamic law, which can adapt to the social and moral needs of the community. This study recommends an ethical and historical approach to interpreting legal hadiths in order to produce religious practices that are both relevant and just.